Population pharmacokinetics of intravenous Erwinia asparaginase in pediatric acute lymphoblastic leukemia patients - Sebastiaan D.T. Sassen; Ron A.A. Mathôt; Rob Pieters; Robin Q.H. Kloos; Valérie de Haas; Gertjan J.L. Kaspers; Cor van den Bos; Wim J.E. Tissing; Maroeska te Loo; Marc B. Bierings; Wouter J.W. Kollen; Christian M. Zwaan; et al. (Haematologica, 2017)
Erwinia asparaginase is an important component in the treatment of pediatric acute lymphoblastic leukemia. A large variability in serum concentrations has been observed after intravenous Erwinia asparaginase. Currently, Dutch Childhood Oncology Group protocols dose alterations are based on trough concentrations to ensure adequate asparaginase activity (≥100 IU/L). The aim of this study was to describe the population pharmacokinetics of intravenous Erwinia asparaginase to quantify and gather insight into inter-individual and inter-occasion variability. The starting dose was evaluated on the basis of the derived population pharmacokinetic parameters. In a multicenter prospective observational study, a total of 714 blood samples were collected from 51 children (age 1–17 years) with acute lymphoblastic leukemia. The starting dose was 20,000 IU/m2 three times a week and adjusted according to trough levels from week three onwards. A population pharmacokinetic model was developed using NONMEM®. A 2-compartment linear model with allometric scaling best described the data. Inter-individual and inter-occasion variability of clearance were 33% and 13%, respectively. Clearance in the first month of treatment was 14% higher (P